Design and Development of a Radiation Survey and Rescue Robot with Shielding of Electronic Equipment from Radiation Damage with Image Radiation Mapping Facility - Md. Sifatul Muktadir; Md. Nazmul Hassan; Md. Saimon Siddique; Dewan Nazmun Nur; Altab Hossain; Ahnaf Tahmid Chowdhury (International Journal of Nuclear Security, 2024)
The use of remote-controlled robots in emergency fields is a necessary requirement at present, which includes the nuclear engineering field because the radioactive environment creates adverse effects on human health. This work describes the development of a remotely controlled rover capable of detecting ionizing radiation, isolating radiation sources using a robotic arm, and sufficient shielding for its internal components. A custom-made Geiger–Muller counter has been used to detect ionizing radiation. The radioactive environment is not only harmful for humans but also can cause severe damage to the electronic circuit mounted on the robot. Therefore, a custom concrete material sandwiched between lead sheets has been employed to shield internal electronic components. The rover is connected to a web application to visualize data such as background radiation, location, and surveillance; thus, the operator can perform their actions from a remote and safe location by using Internet of Things devices. The rover is expected to be used in nuclear facilities to monitor background radiation data and help workers to minimize exposure from unshielded radiation sources. Other than this use, in case of emergency, the rover can find the radiation source in a highly radioactive environment, pick it up using its arm, and isolate it by putting it on the shielded box mounted over the rover. In a nuclear medicine facility, the rover can handle radiation sources and reduce unwanted exposure to occupational exposure groups.
Keywords: Radiation detection robot; radiation shielding; IoT devices